2006
DOI: 10.1111/j.1567-1364.2006.00130.x
|View full text |Cite
|
Sign up to set email alerts
|

Anin vitroassay to study the transcriptional response during adherence ofCandida albicansto different human epithelia

Abstract: Adhesion to mammalian epithelia is one of the prerequisites that are essential to accomplish pathogenesis of Candida albicans in the mammalian host. In this context C. albicans is able to adhere to a plethora of different cell types providing different microenvironments for colonization. To study the response of C. albicans adhering to different surfaces on the transcriptional level we have established an in vitro adhesion assay exploiting confluent monolayers of the human colorectal carcinoma cell line Caco-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(62 citation statements)
references
References 30 publications
2
60
0
Order By: Relevance
“…To our knowledge, the transcriptional response of C. albicans to endothelial cells has not been determined previously. However, two other groups of investigators have studied the response of this organism to contact with vaginal, cervical, and intestinal epithelial cell lines as compared to polystyrene (60,65). Both groups found that contact with epithelial cells caused only a two-to fourfold change in C. albicans gene transcript levels.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, the transcriptional response of C. albicans to endothelial cells has not been determined previously. However, two other groups of investigators have studied the response of this organism to contact with vaginal, cervical, and intestinal epithelial cell lines as compared to polystyrene (60,65). Both groups found that contact with epithelial cells caused only a two-to fourfold change in C. albicans gene transcript levels.…”
Section: Discussionmentioning
confidence: 99%
“…The ability to adhere is a biological phenomenon that is widely distributed and shared by many pathogens, enabling the colonization of their respective habitats. 15,16 Some adhesins have been described for P. brasiliensis, such as gp43, 17,18 glyceraldehyde-3-phosphate dehydrogenase, 19 triose phosphate isomerase, 20 enolase, 21,22 a 32-Kda hydrolase, 23,24 malate synthase, 25 isocitrate lyase 26 and the 14-3-3 protein (30 KDa) 27,28 ; this last adhesin is the focus of the present study.…”
Section: Introductionmentioning
confidence: 99%
“…A quantitative adhesion assay and an investigation of adhesion kinetics was performed in polystyrene 24-well plates (ThinCert-24well-Multiwell-Platte, Greiner Bio-one) with 5 selected time points (0, 30, 60, 120, 240 min; time point 0 min was used as the background control), according to the published protocol of Sohn et al [23]. For this experiment, a polystyrene plastic surface and RHE were used as described by Dieterich et al [14] with the minor modifications reported by Sohn & Rupp [25].…”
Section: Adhesion Assay and Adhesion Kineticsmentioning
confidence: 99%
“…Cells were cultivated at 37°C under 5% CO 2 and at saturated humidity up to 80% confluence. Cell cultures were then split 1:5 using standard methods [23,24] and distributed into the 24-well plates for the adhesion assay, as well as plating onto collagen-coated surfaces for the adhesion assay and invasion experiment, as described below.…”
Section: Preparation Of the Monolayer With Caco-2 And Tr 146 Cell Linesmentioning
confidence: 99%